Importance of R+D+i+e proposals in the rescue of ancestral values to manage water resources - Lizcano-Chapeta, Carlos J. (2021)
This article was generated as the product of a doctoral study and its purpose was to describe the importance of Research-Development-Innovation-Entrepreneurship (R+D+i+e) ​​projects as research and development mechanisms to rescue values ​​and traditions of ancestral peoples towards a comprehensive management of water sources. Documentary research was used, examining works by other authors and theoretical postulates related to the subject. Likewise, a descriptive research type was carried out. Content analysis and hermeneutics were constituted as processes for the analysis of data and information. The results showed that there are several types of innovative projects that arise from ideas to seek to solve a problem, improve a product or service. For this reason, the innovative ecological project that seeks to develop knowledge committed to the preservation of the natural and environmental heritage was highlighted. It was concluded that with R+D+i+e projects, the university institution wants to transfer the understanding of the current state of water sources to assess what the State and indigenous communities can do together through the projects. ecological, transforming the procedures of preservation and care of the water.